Effect of pumping chamber on performance of non-overload centrifugal pump - Gu, Yun-qing; Mou, Jie-gang; Dai, Dong-shun; Zheng, Shui-hua; Wu, Deng-hao; Jiang, Lan-fang; Shi, Han-yu; Wang, Evan (Journal of Central South University, 2015)
In order to specify the characteristics of un-overloaded centrifugal pumps, the IH100-65-200 pump was chosen as the model pump. Different calculation models for centrifugal pumps were established under different pumping chamber sectional parameters. In the numerical simulation of the centrifugal pumps flow field, the shaft power, head, efficiency, and the changes of the internal flow field under different sectional areas and sectional shapes were studied with the RNG k - ε turbulence model, and the influence of the pumping chamber section characteristics of the non-overloaded centrifugal pumps were analyzed. The results show that sectional areas have a significant impact on the non-overload characteristics of centrifugal pumps. The shaft power and head of centrifugal pump are increasing with a lager sectional area, by which the gradient of head curves decreases. The efficiency is improved under a large flow rate condition, but the head and the efficiency are reduced at a small flow rate. It is also observed that the sectional shapes have less influence on the shaft power, the hydraulic performance and flow field characteristics of a centrifugal pump.